Extreme drug resistant A.baumannii associated with CLA-BSI in Kanpur - Pal, Nidhi; Sujatha, R. (International Journal of Research in Medical Sciences, 2017)
Background: Nosocomial bloodstream infection on the critically ill patients has been associated with high mortality. Central venous catheters (CVC) have become essential in the management of patients who are critically ill and those who require long-term medical care. This study was conducted to determine the Central line associated blood stream infections (CLA-BSIs) due to A.baumannii its risk factors and antibiotic resistant patterns. Methods: A total of 52 samples (blood or central line tip) were received from patients with a clinical diagnosis of sepsis after central venous catheterization. The semi quantitative method was used for catheter tip culture. Bacterial identification and antibiotics resistant pattern was performed by Standard microbiological protocol. Results: Of 52 test samples (blood or central line tip), 2 pathogenic strains were isolated from blood, 2 strains of A.baumannii isolated from catheter tips were colonizer and 3 strains of A.baumannii were pathogenic which caused CLA-BSI. The rate of CLABSI due A.baumannii was 11.11 per 1000 catheter days. All A.baumannii were extreme drug resistant (XDR). They only sensitive for polymyxins and tegicyclines. Conclusions: Central venous catheters are increasingly being used in critical care and have been directly related to patient mortality and morbidity. Microbiological surveillance may guide management of multidrug resistant isolates and its complications. Proper infection control practices can reduce the nosocomial infection rate.